Estuarine mangrove niches select cultivable heterotrophic diazotrophs with diverse metabolic potentials—a prospective cross-dialog for functional diazotrophy - Mondal, Sumana; Biswas, Biswajit; Chowdhury, Rajojit; Sengupta, Rudranil; Mandal, Anup; Kotal, Hemendra Nath; Giri, Chayan Kumar; Ghosh, Anjali; Saha, Subhajit; Begam, Mst Momtaj; Mukherjee, Chandan; Das, Ipsita; et al. (Frontiers in Microbiology, 2024)
Introduction Biological nitrogen fixation (BNF), an unparalleled metabolic novelty among living microorganisms on earth, globally contributes ~88-101 Tg N year−1 to natural ecosystems, ~56% sourced from symbiotic BNF while ~22-45% derived from free-living nitrogen fixers (FLNF). The success of symbiotic BNF is largely dependent on its interaction with host-plant, however ubiquitous environmental heterotrophic FLNFs face many limitations in their immediate ecological niches to sustain unhindered BNF. The autotrophic FLNFs like cyanobacteria and oceanic heterotrophic diazotrophs have been well studied about their contrivances acclimated/adapted by these organisms to outwit the environmental constraints for functional diazotrophy. However, FLNF heterotrophs face more adversity in executing BNF under stressful estuarine/marine/aquatic habitats. Methods In this study a large-scale cultivation-dependent investigation was accomplished with 190 NCBI accessioned and 45 non-accessioned heterotrophic FLNF cultivable bacterial isolates (total 235) from halophilic estuarine intertidal mangrove niches of Indian Sundarbans, a Ramsar site and UNESCO proclaimed World Heritage Site. Assuming ~1% culturability of the microbial community, the respective niches were also studied for representing actual bacterial diversity via cultivation-independent next-generation sequencing of V3-V4 rRNA regions. Results Both the studies revealed a higher abundance of culturable Gammaproteobacteria followed by Firmicutes, the majority of 235 FLNFs studied belonging to these two classes. The FLNFs displayed comparable selection potential in media for free nitrogen fixers and iron-oxidizing bacteria, linking diazotrophy with iron oxidation, siderophore production, phosphorus solubilization, phosphorus uptake and accumulation as well as denitrification. Discussion This observation validated the hypothesis that under extreme estuarine mangrove niches, diazotrophs are naturally selected as a specialized multidimensional entity, to expedite BNF and survive. Earlier metagenome data from mangrove niches demonstrated a microbial metabolic coupling among C, N, P, S, and Fe cycling in mangrove sediments, as an adaptive trait, evident with the co-abundant respective functional genes, which corroborates our findings in cultivation mode for multiple interrelated metabolic potential facilitating BNF in a challenging intertidal mangrove environment.